ETHNOMATHEMATICS IN PERSPECTIVE OF SUNDANESE CULTURE - Atje Setiawan Abdullah (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2017)
This study is an exploratory research aims to find and know about a phenomenon by exploration. Therefore, the approach used in this study is ethnographic approach, an empirical and theoretical approach to get description and deep analysis about a culture based on field study. From the sustainable interviews and confirmation about field research with some community leaders in Cipatujah district, Tasikmalaya regency and in Santolo Pameungpeuk beach, Garut regency; it is found that Ethnomathematics is still widely used by Sundanese people especially in rural areas: the use of measurement units, mathematical modeling, and the use of clock symbols. The results of this study can be useful for Sundanese people and the government of West Java in education, cultural services, and tourism. Keywords: Ethnomathematics, Unit Calculation, Modeling, Symbolic TimeÂ DOI:Â http://dx.doi.org/10.22342/jme.8.1.3877.1-15